The concept of aurah: Islamic dressing code and personal grooming according to fiqh law / Zanirah Mustafa@Busu, Siti Fatimah Tasir and Nor Asmira Mat Jusoh - Mustafa@Busu, Zanirah; Tasir, Sıtı Fatimah; Mat Jusoh, Nor Asmira (2018)
The method and manner of dressing, whether it is halal or haram have been extensively discussed by many scholars to ensure that the clothes Muslims wear go beyond covering their bodies; it also has to do with the well-being of the individuals as well as the community. All the dress codes specified by Allah and His Messenger form the guiding principles for Muslims as part of their way of life. This article discusses the dressing code in terms of clothing and accessories in Islam for both men and women. This code illustrates what is allowed and not allowed in the selection of clothing and accessories as well as the justifications for obeying this code in daily life. This study covers the actual definition of the concept of aurah according to Islam, women's hijab and veil, jewelry for women and men, and the dress codes of women and men. The findings of the study indicate that in Islam, fashion involving clothing and accessories can fulfil the current needs of society as long as the dress code is adhered to.